Adhesion prevention in reabsorbable polyethylene glycol hydrogel (Coseal®) coated polypropylene mesh in rabbits - Quinino,Reynaldo Martins e (2013)
PURPOSE: To evaluate of postoperative adhesion prevention and inflammatory response to polypropylene mesh, coated with reabsorbable hydrogel of polyethylene glycol (Coseal®) in contact with small bowel in an experimental model in rabbits. METHODS: Twenty female rabbits underwent laparotomy to implant two polypropylene meshes, 2x1cm, in the right and left flanks. The right mesh was protected with Coseal® spray (Group 1) and the left mesh received no treatment after implantation (Group 2). Thirty days after implantation, the rabbits underwent laparoscopy for adhesion analysis; the prosthesis were removed en bloc with the adjacent tissue for microscopic analysis of inflammation. Statistical analysis used the Mann-Whitney test. RESULTS: There was adhesion formation in five meshes (36%) from Group 1 and in 14 meshes (100%) from Group 2, with statistical significance (p<0.01). There were no differences in the inflammatory response, fibrosis, foreign body reaction, presence of collagen and type of inflammatory cells between the two groups. CONCLUSION: Polypropylene mesh coated with Coseal® showed a significantly lower rate of adhesion formation when compared with uncoated meshes, without interfering with inflammatory response.